Exploration of Batak Culture as Sources of Learning Batak Toba Dance - Yusnizar Heniwaty; Sitti Rahmah (BIRCU, 2022)
This study describes cultural exploration that is used as a source of learning, this is related to how to introduce culture which can be done through art learning in formal activities and informal activities. Through the exploration of traditional culture, in this case the art of dance, efforts to preserve, introduce, inherit, and develop traditional arts become part of strengthening attitudes in understanding norms, values in society.